2011
DOI: 10.1007/s10103-011-1013-z
|View full text |Cite
|
Sign up to set email alerts
|

Photoinactivation of cell-free human immunodeficiency virus by hematoporphyrin monomethyl ether

Abstract: Human immunodeficiency virus (HIV) particles that remain in the blood of patients are frequently ignored as targets for AIDS treatment. We therefore investigated the use of photodynamic therapy (PDT) with hematoporphyrin monomethyl ether (HMME) as a means of inactivating cell-free HIV in vitro. Virus particles including HIV-1IIIB, resistant HIV-1 variants, HIV-1 clinical variants, and HIV-2 variants were incubated with HMME for 40 min, followed by irradiation with a 630-nm semiconductor laser at an energy dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Photodynamic therapy (PDT) is widely used for treating tumors on the surface of the skin or in body cavities, including tumors of the skin, head, and neck areas, as well as solid tumors that can be accessed with relative ease, such as tumors of the esophagus, lungs, larynx, and uterine cervix. [12][13][14] PDT has also been developed recently for application to non-solid tumors such as leukaemia, 15 and for AIDS 16 and infectious disease. 17 This therapeutic approach involves the administration of a tumor-localizing PS, by intravenous injection or external application, and the subsequent targeted activation of this PS by exposure to light of a specic wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is widely used for treating tumors on the surface of the skin or in body cavities, including tumors of the skin, head, and neck areas, as well as solid tumors that can be accessed with relative ease, such as tumors of the esophagus, lungs, larynx, and uterine cervix. [12][13][14] PDT has also been developed recently for application to non-solid tumors such as leukaemia, 15 and for AIDS 16 and infectious disease. 17 This therapeutic approach involves the administration of a tumor-localizing PS, by intravenous injection or external application, and the subsequent targeted activation of this PS by exposure to light of a specic wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is a therapeutic modality not only applicable for the treatment of superficially localized tumors, but is also associated with the antiviral and bactericidal properties of dyes [2][3][4]. PDT can be defined as the systemical, local or topical administration of a nontoxic drug or dye known as photosensitizer (PS), which acquires the desired activity only when it is excited by light of an appropriate wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…The inactivating effect of PDT on HIV, HBV, and other blood‐borne pathogens in vitro has been confirmed. Our team also performed a series of cell experiments with HIV that verified the significant inactivating effect of PDT on various HIV subtypes and also on resistant mutant forms . Although experimental results in vitro suggest that PDT has great potential to inactivate viral blood pathogens, in vivo studies have not yet been reported.…”
Section: Discussionmentioning
confidence: 95%